Learning technology with using of cognitive graphics cards - TULASHVILI, Iurii; OLEKSIV, Nataliia (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2016)
The article deals with the need of improvement of the system of training engineering teachers of computer disciplines on the base of scientifically based didactic innovative technologies. This article also analyzes the existing learning technologies and pedagogical aspects of technology of construction and use of cognitive maps in educational activities. Actuality of their application and mapping software capabilities is proved, the model of cognitive maps is investigated.